Deskripsi Kemampuan Berpikir Kritis Siswa Dalam Pemecahan Masalah Bentuk Aljabar Di Kelas VII Mts Al-Aziziyah Putra Tahun Ajaran 2021/2022 - Iqrimi Ziarati; Laila Hayati; Nilza Humaira Salsabila; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe students' critical thinking skills in solving algebraic form problems in class VII MTs Al-Aziziyah Putra for the 2021/2022 school year. The methods used in this study were description tests and interviews. The subjects in this study were 26 students. This type of research is descriptive qualitative. The indicators of critical thinking ability include interpretation, analysis, evaluation and inference. Based on data analysis, it can be concluded that: (1) The number of subjects in the high category is 2 students, with a percentage of 7.70% (2) The number of subjects in the medium category is 6 students, with a percentage of 23.07% (3) The number of subjects in the low category is 8 students , with a percentage of 30.77% (4) Furthermore, the number of subjects with a very low category is 10 students, with a percentage of 38.46%. The results of the research on students' critical thinking skills are 48.11%, the percentage value is obtained from students' critical thinking skills on the interpretation indicator obtained 75.7% with the highest percentage, students' critical thinking skills on the analytical indicator obtained 60% with the second highest percentage , students' critical thinking skills on the evaluation indicator were obtained by 30.12% with the third achievement level percentage, then students' critical thinking skills on the inference indicator obtained 26.60% with the least percentage of achievement levels.